GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 108976 species occurrences available in GBIF matching the query: Country: Myanmar. The dataset includes 108976 records from 357 constituent datasets: 1 records from Phthiraptera. 1 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 3 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 274 records from Phanerogamic Botanical Collections (S). 4 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 1 records from Bee Biology and Systematics Laboratory. 2 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 5 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 7 records from Herpetile collection, Natural History Museum, University of Oslo. 14 records from MVZ Mammal Collection (Arctos). 1229 records from CAS Entomology (ENT). 3095 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from CHAS Ornithology. 3 records from SAIAB: National Fish Collection (1880-2008). 451 records from University of California Museum of Paleontology. 123 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 50 records from Naturalis Biodiversity Center (NL) - Crustacea. 5 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Orthopteroidea. 2871 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 304 records from Australian National Wildlife Collection provider for OZCAM. 3 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 9 records from Zoology (Museum of Evolution - Uppsala). 293 records from Field Museum of Natural History (Zoology) Mammal Collection. 2 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 4 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 2113 records from Museum of Comparative Zoology, Harvard University. 379 records from Australia's Virtual Herbarium. 9212 records from EOD - eBird Observation Dataset. 1 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 5 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 15 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 223 records from AntWeb. 32 records from CSIRO Ichthyology provider for OZCAM. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 16 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Museum Victoria provider for OZCAM. 353 records from CAS Invertebrate Zoology (IZ). 46 records from CONN. 1408 records from CAS Ichthyology (ICH). 38 records from NRM-Herpetology. 300 records from Herbarium of The New York Botanical Garden. 1 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 1 records from Heteroptera. 94 records from SBMNH Vertebrate Zoology. 46 records from Lepidoptera specimen database of Japan. 1 records from Ehime University Coleoptera Collection. 11 records from Natural History Museum, Vienna - Herbarium W. 74 records from Macaulay Library Audio and Video Collection. 4 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 1 records from Herbarium Senckenbergianum (FR) - Fungi. 3 records from Collection Malakologie - SNSD. 4 records from UWBM Ornithology Collection. 603 records from Paleobiology Database. 2 records from Bohart Museum of Entomology, UCD. 91 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 3 records from Collection of Heteroptera. 95 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 3 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 1010 records from Fishbase. 1 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from NPL collections. 223 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 35 records from NCSM Fishes Collection. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 8 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 1 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 11 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 10 records from Naturalis Biodiversity Center (NL) - Mammalia. 10 records from Ichthyology Collection - Royal Ontario Museum. 173 records from CAS Ornithology (ORN). 1 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 5 records from DMNS Marine Invertebrate Collection (Arctos). 6 records from Wildbook for Whale Sharks. 3 records from mel. 4 records from Entomological collection of the National Museum. 5 records from PRECIS. 2 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 1 records from Colección de Zoología Invertebrados - Otros invertebrados. 4 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 1 records from ALCB - Herbário Alexandre Leal Costa. 14000 records from NMNH occurrence DwC-A. 5 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 1 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 24 records from Diveboard - Scuba diving citizen science observations. 1 records from A review of the genus Mystrium (Hymenoptera: Formicidae) in the Indo-Australian region.. 107 records from AlgaTerra. 207 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 5 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History. 4 records from Herbaria of the University and ETH Zürich. 58 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1 records from The Lichen Collection at the Botanische Staatssammlung München. 18 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 4 records from KUBI Mammalogy Collection. 157 records from Lund Museum of Zoology - Insect collections (MZLU). 41 records from The avian collection at the Natural History Museum, Oslo, Norway. 344 records from Field Museum of Natural History (Zoology) Bird Collection. 61 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4 records from Algae (S). 1 records from Lund Museum of Zoology (MZLU). 2 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 9 records from iNaturalist research-grade observations. 36 records from UCBG TAPIR Provider. 151 records from Invertebrates Collection of the Swedish Museum of Natural History. 3 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 6 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 1 records from Mammal collection, Natural History Museum, University of Oslo. 601 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 5 records from Canadian Museum of Nature Herbarium. 1 records from Estonian University of Life Sciences. 2 records from Essig Museum of Entomology. 1 records from TNHC Ichthyology Collection. 2 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from Global Butterfly Information System (GloBIS). 49 records from Illinois Natural History Survey Insect Collection. 85 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 140 records from The Brown University Foraminiferal Data Base (BFD). 26 records from naturgucker. 11 records from CAS Mammalogy (MAM). 10 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 119 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 15 records from Northern Territory Museum and Art Gallery provider for OZCAM. 238 records from LACM Vertebrate Collection. 575 records from Nationaal Herbarium Nederland. 7 records from Collection Crustacea - ZIM Hamburg. 1 records from Collection Porifera - ZMB. 16 records from Collection Vermes - ZMB. 23 records from Western Australian Museum provider for OZCAM. 10080 records from Natural History Museum (London) Collection Specimens. 45 records from Collection Ichthyologie - SNSD. 38 records from Edaphobase. 56 records from Australian National Herbarium (CANB). 11 records from CBS fungi strains. 8 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 6 records from Mollusca specimens of Toyama Science Museum. 95 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 2 records from Jardin botanique de Montréal (JBM). 1 records from Bird Collection of Yokosuka City Museum. 32 records from Insect Collection of Yokosuka City Museum. 67 records from Fossil (WSHN-FO). 194 records from Missouri Botanical Garden. 5 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 3 records from Lepidoptera - SNSD. 204 records from SysTax - Zoological Collections. 2 records from Collection Crustacea - SNSD. 513 records from CABI Bioscience Fungus Collection. 1 records from Herps Specimens. 3 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 8 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 72 records from Hexacoral Database. 1 records from Kashihara City Museum of Insect. 20 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 6 records from Invertebrate Zoology Division, Yale Peabody Museum. 1 records from TTU Mammals Collection. 1 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 5 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 3 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 2 records from NCOS1959_Crustacea (OBIS China). 1 records from NCOS1959_Mollusca (OBIS China). 1 records from Mosquito Occurrence Dataset. 219 records from WFVZ Bird Collections. 158 records from DORSA - German Orthoptera Collections. 74 records from Mosses (S). 1 records from Field Museum of Natural History (Botany) Lichen Collection. 1 records from Bryophyte herbarium, Trondheim (TRH). 52 records from UMZC Zoological Specimens. 475 records from AMNH Herpetology Collections. 1 records from CM Herps Collection. 1 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 3 records from Iziko. 1 records from Collection Oligochaeta - ZIM Hamburg. 39 records from Collection Crustacea - ZMB. 236 records from SMNK Mantid Collection. 11 records from Naturhistorisches Museum Mainz, Zoological Collection. 7 records from Myriapoda - SMF. 105 records from An updated checklist of aquatic plants of Myanmar and Thailand. 46 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from Collection Bernstein - SMF. 15 records from Collection Herpetologie - SNSD. 2 records from Collection Ornithologie - SNSD. 102 records from The Himalayan Uplands Plant database (HUP Version 1). 22 records from Parasitic Platyhelminthes Collections. 4 records from AIMS - Bioresources Library (OBIS Australia). 7 records from iziko South African Museum - Shark Collection (AfrOBIS). 1 records from Naturalis Biodiversity Center (NL) - Coleoptera. 6 records from Fish specimens. 1 records from DSMZ Prokarya Collection Catalogue. 1262 records from ORN. 1751 records from MAL. 1 records from Natural History Museum, University of Tartu. 8 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 2 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 3 records from Therevid PEET Project. 20 records from Entomology Division, Yale Peabody Museum. 3 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 38 records from Vertebrate Paleontology Division, Yale Peabody Museum. 102 records from Collection Pisces SMF. 146 records from Collection Mammalia SMF. 2465 records from AMNH Mammal Collections. 10 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 19 records from A review of the species in the Apogon fasciatus group with a description of a new species of cardinalfish from the Indo-West Pacific (Perciformes: Apogonidae).. 26 records from Queensland Museum provider for OZCAM. 1 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 5 records from Shellfish specimens in the NISHINOMIYA SHELL MUSEUM, Japan.. 296 records from RBINS collections. 7 records from CABI Bioscience Genetic Resource Collection. 311 records from herpetology. 4 records from The AAU Herbarium Database. 2509 records from NODC WOD01 Plankton Database. 5 records from Bishop Museum Data (OBIS distribution) (USOBIS). 1 records from Botanic Garden of the Finnish Museum of Natural History. 1870 records from MICROBIS database. 1 records from Mammal specimens. 76 records from NSW herbarium collection. 147 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 10 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 1030 records from invertebratezoology. 2 records from MfN Fish Collection, Zoology. 83 records from Herpetology. 92 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 1 records from Mammal specimen database of Kanagawa Prefectural Museum of Natural History. 17 records from Collection Aves (bird skins) SMF. 20 records from SINGER Coordinator. 7 records from SMNS Herpetologie. 3 records from CM Birds Collection. 1331 records from Snow Entomological Museum Collection. 3 records from Coleoptera collection of National Museum of Nature and Science. 7 records from Australian National Insect Collection. 1 records from Mammalogy Collection - Royal Ontario Museum. 21 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 1 records from Allan Herbarium (CHR). 57 records from UF FLMNH Ichthyology. 150 records from Geneva Herbarium – General Collection (G). 1 records from ENBI-Dataset of GART-GloBIS. 3 records from International Fossil Shell Museum (NL) - Mollusca Collection. 1 records from National Museum of Natural Science. 63 records from Bird Collection of Museum and Institute of Zoology PAS. 4 records from UWFC Ichthyology Collection. 70 records from Academy of Natural Sciences OBIS Mollusc Database. 3 records from South African Institute for Aquatic Biodiversity - Fish Collection (AfrOBIS). 1 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 9 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 1 records from MSUM Ichthyology and Herpetology Collections. 19 records from Fish collection of National Museum of Nature and Science. 13 records from Freshwater Fish Specimens of Lake Biwa Museum. 8 records from UCD BOTANICAL CONSERVATORY. 4 records from University of Alberta Ichthyology Collection (UAMZ). 43 records from Herbarium Berolinense. 1 records from Lichen Herbarium Berlin. 14 records from Biologiezentrum Linz. 176 records from The System-wide Information Network for Genetic Resources (SINGER). 58 records from IndOBIS, Indian Ocean Node of OBIS. 2 records from HBGSpermatophyta - Herbarium Hamburgense. 471 records from Harvard University Herbaria. 4 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from Bird specimens in Gifu Prefectural Museum. 264 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 7 records from UMMZ Herpetology Collection. 2 records from University of British Columbia Herbarium (UBC) - Algae Collection. 7 records from Field Museum of Natural History (Botany) Seed Plant Collection. 3 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 1 records from Homoptera. 7 records from DUKE Bryophyte Collection. 10 records from Collection Aves (spirit preserved) SMF. 31 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 3 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 1 records from Two new glyptosternine catfishes (Teleostei: Sisoridae) from Vietnam and China.. 82 records from Field Museum of Natural History (Zoology) Fish Collection. 1 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 1 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 229 records from Bernice P. Bishop Museum. 79 records from United States National Plant Germplasm System Collection. 22 records from Fish Collection of Natural History Museum and Institute, Chiba. 11 records from Itami City Museum of Insects. 5 records from Chinese Institute of Biology - Chinese Academy of Sciences. 3 records from Field Museum of Natural History (Botany) Bryophyte Collection. 321 records from Collection Arachnology SMF. 1 records from Collection Coleoptera SMF. 86 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 18 records from Animal Sound Archive. 14 records from Akysis pulvinatus, a new species of catfish (Siluriformes: Akysidae) from southern Thailand.. 6 records from DMNH Birds. 16 records from Akysis longifilis, a new species of catfish (Teleostei: Akysidae) from Myanmar.. 8 records from Herpetology Collection - Royal Ontario Museum. 177 records from Naturalis Biodiversity Center (NL) - Mollusca. 5 records from A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides.. 423 records from Vascular Plant Herbarium, Oslo (O). 3 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 7 records from Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 72 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 92 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Insect specimens database of Shizuoka Prefecture Museum of Natural History. 35 records from North Carolina State Museum of Natural Sciences Fishes Collection. 2 records from Sukkulentensammlung Zürich. 1 records from Botany Division, Yale Peabody Museum. 61 records from Collection Mollusca SMF. 18 records from Collection Crustacea SMF. 15 records from Database of Native Plants in Taiwan. 3590 records from AMNH Bird Collection. 140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 3 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 54 records from MVZ Egg and Nest Collection (Arctos). 1 records from A taxonomic revision of the Asian endemic subgenus Physocrema of the genus Crematogaster (Hymenoptera: Formicidae).. 37 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 4 records from Lund Botanical Museum (LD). 270 records from Geographically tagged INSDC sequences. 122 records from ECatSym: Electronic World Catalog of Symphyta. 3292 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Pachycondyla nigrita and related species in Southeast Asia.. 1 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 72 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 5589 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from The velvet spiders: an atlas of the Eresidae (Arachnida, Araneae). 10 records from NCSM Invertebrates Collection. 6 records from Entomology at ZMUC, Natural History Musem of Denmark. 152 records from CAS Botany (BOT). 2 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 1 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 406 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Description of a new species of weasel shark, Hemigaleus australiensis n. sp. (Carcharhiniformes: Hemigaleidae) from Australian waters.. 8 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 18 records from UMMZ Birds Collection. 58 records from Botany (UPS). 3981 records from NRM-Fishes. 7 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 1 records from Entomological specimens of Museum fuer Naturkunde und Vorgeschichte Dessau. 59 records from Australian Museum provider for OZCAM. 14 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 11 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 3 records from MVZ Bird Collection (Arctos). 13 records from New Zealand Fungal and Plant Disease Collection (PDD). 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Porifera. 3 records from Fish collection, Natural History Museum, University of Oslo. 1 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 4 records from Instituto de Botánica Darwinion. 26 records from CUMV Bird Collection (Arctos). 72 records from South Australian Museum Australia provider for OZCAM. 4 records from CUMV Reptile Collection (Arctos). 2 records from A revision of the gobiid fish genus Trypauchen (Gobiidae: Amblyopinae).. 6 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 1 records from Bryophyte herbarium, Göttingen (GOET). 17240 records from CAS Herpetology (HERP). 4 records from Pseudolaguvia ferula, a new species of sisoroid catfish (Teleostei: Erethistidae) from India.. 266 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 230 records from KUBI Herpetology Collection. 1 records from Nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 21 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 3 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 1 records from Clubionidae from Laos and Thailand (Arachnida: Araneae). 140 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 88 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 45 records from Herbarium WRSL, Main Collection. 1 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 29 records from Fungi (S). 86 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris).
Keywords: GBIF; biodiversity; species occurrences